Reconstructive Rhinoplasty - L. M. Bariar; J. K. Sinha; F. M. Tripathi; V. Bhattacharya (Indian Journal of Plastic Surgery)
Twelve cases of injury nose, treated in the Plastic Surgery Section at University Hospital, Varanasi, are presented. Traumatic etiology was seen in eight cases (66.66&), and one each was due to electric burn, rat bite, human bite and post surgical. One case of lower half avulsion was seen without Joss of tissue. Others having loss of tissue of different component of nose, were treated by flaps and skin grafts. Primary closure was done in the one presenting without loss of tissue. The evaluation of results have been discussed.